PERTANGGUNGJAWAB PIDANA RUMAH SAKIT TERKAIT DENGAN TINDAK PIDANA LINGKUNGAN HIDUP YANG DILAKUKAN PEGAWAI RUMAH SAKIT - Hanna Niken Sihotang; Alvi Syahrin; Muhammad Eka Putra; Utary Maharany (Universitas Sumatera Utara, 2015)
ABSTRACT Health as one of the elements of the common welfare must be realized through a variety of health in the context of the development of a comprehensive and integrated health supported by a national health system.. In terms of obtaining the authorization for hospital waste treatment there are also requirements that include environmental health efforts (UKL), environmental monitoring efforts (UPL), and or environmental impact assessment (EIA) which is regulated in the Act no.44 of 2009 on hospital. However, if the hospital does not have a license as referred to in Article 25 paragraph (1) it will be subject to criminal sanctions in accordance with Article 62 of Law No. 44 Year 2009 In violation Enviromental Law. Hospital sued in violation of Article 102 Enviromental Law. Then the responsibility of the administrator in the event of environmental contamination associated with hospital waste hospital administrators the responsibility associated with environmental crime in accordance with Article 117 which states that if criminal charges are filed with the leader giving the order or a criminal offense in this case was referred to committee in Article 116 paragraph (1) letter b, then a sentence of imprisonment and imposed a fine is increased by one third. Enviromental Law itself regarding criminal liability of legal entities pollutant / destroyer of the environment which is as set out in Article 116, which is well within the legal person as well as against those who gave the order or who acts as a leader in an action (destroy / pollute the environment) or against both. Accountability of hospitals associated with environmental crime set in Article 119 Enviromental Law that the entity may be subject to additional criminal or disciplinary action. Hospital administrators and accountability related to environmental crime under Article 116 paragraph (1) letter a and b. Keywords : criminal liability, environmental crime, enviromental law